Diagnóstico numérico de vigas Vierendeel formadas por perfis tubulares metálicos de seção circular - Resende, Anne Danielle Ferraz Lopes (2008)
Vierendeel trusses are framed structures having parallel chord members used in several types of buildings where lighting, ventilation and architectural definitions do not permit using cells with diagonal web members as in classic trusses. This work presents a study of Vierendeel trusses formed by hollow structural sections considering the global structure behavior and the local "T" connections under axial force and bending. The finite element method is use to assess the whole structure through software ANSYS. As the manual CIDECT and some authors indicate a simplified design by the introduction of hinges in strategic points, it is perform a comparison between this model and the simplified model called real. This assessment is indicated by the CIDECT nº 1 manual and by several authors, applying the computation of the stress and displacements. Numerical study cases are presented for better understanding over this structural type and gaining of knowledge about the effect generated by the ovalization of the tubes. Computation development of the connections and members are presented for these cases to make use the CIDECT nº 1 manual and the softwares HSS_connex 1.02 and GESTRUT, both in accordance with Canadian's rule CAN/ CSA-S16.1-94. Several analyses are presented as means of showing the relations between span and height of Vierendeel trusses and the interference of the tubes in stress distribution. This work is a contribution to the hollow structural section connections study, still little used in Brazil.